Population Structure Durian (Durio zibethinus L.) in Barito River Banks Sungai Gampa Village Barito Kuala Regency - Muhammad Ilham Setiyawan; Dharmono Dharmono (Pattimura University, 2026)
Study of population structure is important in determining the status of a plant. Durian (Durio zibethinus L.) is commonly used by the village community of Sungai Gampa as a boundary for rice fields, in addition to its fruit and seeds, which are edible. The study aims to describe the population structure of durian (Durio zibethinus L.) along the banks of the Barito river in the village of Sungai Gampa. This is a quantitative descriptive study using data collection using transcet techniques along the Barito river. The results show that the pyramid formed is a polygonal pyramid or a pyramid with a wide base, meaning that the population of young individuals is greater than that of adult individuals. In addition, durian is included in the